Diagnosis and management of α1-antitrypsin deficiency in Europe: an expert survey. Issue 1 (11th March 2019) - Horváth, Ildikó; Canotilho, Maria; Chlumský, Jan; Chorostowska-Wynimko, Joanna; Corda, Luciano; Derom, Eric; Ficker, Joachim H.; Kneussl, Meinhard; Miravitlles, Marc; Sucena, Maria; Thabut, Gabriel; Turner, Alice M.; et al.
Despite recent improvements, α1 -antitrypsin deficiency (AATD) remains a rarely diagnosed and treated condition. To assess the variability of AATD diagnosis/treatment in Europe, and to evaluate clinicians' views on methods to optimise management, specialist AATD clinicians were invited to complete a web-based survey. Surveys were completed by 15 physicians from 14 centres in 13 European countries. All respondents perceived the AATD diagnosis rate to be low in their country; 77% of physicians believed that ∼15% of cases were diagnosed. Low awareness was perceived as the greatest barrier to diagnosis. Spirometry was considered more practical than quantitative computed tomography (QCT) for monitoring AATD patients in clinical practice; QCT was considered more useful in trials. AAT therapy provision was reported to be highly variable: France and Germany were reported to treat the highest proportion (∼60%) of diagnosed patients, in contrast to the UK and Hungary, where virtually no patients receive AAT therapy. Most clinicians supported self-administration and extended dosing intervals to improve convenience of AAT therapy. This survey indicates that AATD diagnosis and management are highly heterogeneous in Europe; European cooperation is essential to generate data to support access to AAT therapy. Improving convenience of AAT therapy is an ongoing objective. Access to α1 -antitrypsin (α1 -AT) therapy varies in Europe; where available, α1 -AT therapy optimisation is the goal http://ow.ly/YL6m30n4LV3